Seasonal variation of different seminal parameters of breeding buffalo bulls - Hasan Riaz (Revista Científica)
This study evaluated seasonal variation in seminal parameters and post-thaw motility after cryopreservation in buffalo bulls. To conduct this study, five Nili Ravi buffalo bulls were placed at a private semen production unit, Al-Haiwan Sires, Sahiwal, under uniform nutritional and management conditions. Semen samples were taken twice a week from May 2019 to April 2020. A total of 389 ejaculates were collected with the help of a pre- warmed artificial vagina (42ºC) and then transferred to the semen evaluation room. Then, semen ejaculates were evaluated for physical characteristics, including ejaculatory volume, mass motility, individual sperm motility, sperm concentration, number of ejaculates, motility after dilution, and post-thaw motility. Post-thaw semen evaluation was carried out by Computer Assisted Sperm Analyzer (CASA) at the Theriogenology laboratory, UVAS Lahore. Climatic data was also collected from the Regional Meteorological Center, Sahiwal, during the study period. The seminal parameter data of Nili Ravi buffalo bull was analyzed using the analysis of variance in the SPSS 13.0 program. The results showed that season significantly (p<0.05) affected different seminal parameters, as no. of ejaculates/bull, motility after dilution, and number of doses were significantly higher in autumn. In contrast, semen volume and individual motility were highest in spring. Interestingly, sperm concentration was highest in the dry summer compared to other seasons. The sperm motility parameters and motion characteristics of buffalo bulls after post-thaw revealed that total motility, progressive motility, and rapid motility were not affected by season. In contrast, VSL, VCL, and ALH were significantly higher in the spring season than others. In conclusion, it was found that breeding bulls exhibited a seasonal pattern as their seminal parameters were found best in the spring and autumn seasons; however, most post-thaw variables have no seasonal effect.